Short-term results of ABO-incompatible living donor kidney transplantation: comparison with ABO-compatible grafts - Hwang, Jeong Kye (The Korean Surgical Society, 2011)
PURPOSE: ABO incompatible (ABOi) kidney transplantation (KT) has been increasing to compensate for the shortage of organ donors. However, detailed comparative analyses of ABOi KT with ABO compatible (ABOc) KT are still rare. METHODS: This retrospective study compared 12 consecutive ABOi KTs to 50 ABOc KTs that employed the same maintenance immunosuppressive agents during the same period. Comparisons of patient survival, graft survival, graft function, and complications were made until post-transplant day 90. RESULTS: Baseline characteristics of the two groups were similar except for the positivity of panel reactive antibody (12% in the ABOc group vs. 42% in the ABOi group; P = 0.029). There were no significant differences in patient survival, graft survival, post-operative renal function, incidence of acute rejection, infections, or medical and surgical complications. However, bleeding complications were more common in the ABOi group (25%) than versus the ABOc group (6%) (P = 0.08). The preoperative and total hospital stay of the ABOi patients was significantly longer than the ABOc patients (P = 0.001). CONCLUSION: ABOi KT is a viable and safe option for patients whose only donor is blood incompatible, despite the longer preoperative hospital stay for preparation.